2017
DOI: 10.1088/1361-6463/aa9431
|View full text |Cite
|
Sign up to set email alerts
|

Interface between Al2O3and 4H-SiC investigated by time-of-flight medium energy ion scattering

Abstract: The formation of interfacial oxides during heat treatment of dielectric films on 4H-SiC has been studied. The 4H-SiC surface has been carefully prepared to create a clean and abrupt interface to Al 2 O 3 . An amorphous, 3 nm thick, Al 2 O 3 film has been prepared on 4H-SiC by atomic layer deposition and rapid thermal annealing was then performed in N 2 O ambient at 700 °C and 1100 °C during 1 min. The samples were studied by time-of-flight medium energy ion scattering (ToF-MEIS), with sub-nanometer depth resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Thus, resulting in relatively low concentration of oxygen at higher temperatures. This further improves the quality of Al 2 O 3 by crystallizing the material at such high temperatures [24,30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, resulting in relatively low concentration of oxygen at higher temperatures. This further improves the quality of Al 2 O 3 by crystallizing the material at such high temperatures [24,30].…”
Section: Resultsmentioning
confidence: 99%
“…Also, the hysteresis in CV measurements is mostly observed, where the charge trapping levels can be as high as 10 13 cm −2 , which originates from the native defects in atomic layer deposited (ALD) Al 2 O 3 layer and stays near the interface, typically named as border traps [21,22]. In our previous investigations, we found that the annealing of Al 2 O 3 /SiC structure at 1100 °C process temperature keeps the interface intact and reduces the hysteresis, independent of annealing time duration, and forms a thin SiO 2 interfacial layer between Al 2 O 3 and 4H-SiC [23,24]. The formation of SiO 2 at the interface then reduces the positive flatband shift (indicating negative charges at the interface or in the oxide) observed in various studies.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the authors concluded that annealing at 900 • C represented the best option in terms of both surface morphology and dielectric quality. On the other hand, many other papers demonstrated that such high annealing temperatures induce the formation of a thin stoichiometric or sub-stoichiometric silicon oxide interfacial layer [33,[50][51][52]. This oxidation phenomenon can have a detrimental impact on the properties of high-κ/SiC interfaces, including in the case of abrupt Al 2 O 3 /4H-SiC interfaces obtained by ALD growth [40,[53][54][55].…”
Section: Growth Of Amorphous High-κ Oxides On Sicmentioning
confidence: 99%